Multiple Skeletal Deformities in a Middle-Aged Man - Martínez-Méndez, José Hernán; Gutiérrez-Acevedo, Madeleine; Gómez-Cintrón, Ángel A.; Mangual-García, Michelle; Sánchez-Cruz, Alfredo; Trinidad-Hernández, Rafael; Santiago-Núñez, Mónica; Figueroa-Núñez, Carlos; Miranda-Adorno, María de Lourdes; Palermo-Garófalo, Coromoto; Torres-Rafael, Oberto (Puerto Rico Health Sciences Journal, 2015)
A 54-year-old man was seen in our endocrinology clinic with evidence of a limited range of motion in his left foot. He had a history of diabetes mellitus type 2 and atrial fibrillation. His family history included evidence of skeletal deformities in some of his relatives. This could imply the potential existence of a hereditary condition. It is worth noting that spontaneous mutations have been reported in some cases. A pertinent physical examination revealed a surgical scar on the patient’s left knee, a hallux valgus deformity on his left foot with compromised joint function, and painless bony prominences on that same foot. The skeletal survey findings were consistent with multiple hereditary exostoses. Multiple osteochondromatosis (MO) is a rare genetic disorder associated with serious complications that may significantly affect the health related quality of life of anyone having the disorder. To prevent further complications, these patients require long-term follow-up with regular clinical and radiological examinations.